The ANALYSIS OF PHARMACEUTICAL SERVICES IN COMMUNITY PHARMACIES IN DKI DURING COVID-19 PANDEMIC: ANALYSIS OF PHARMACEUTICAL SERVICES IN COMMUNITY PHARMACIES IN DKI DURING COVID-19 PANDEMIC - Karlina, Lina; Sumiyati, Yati; Utami Ramadaniati, Hesty; S. Mardiko, Etty (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
The COVID-19 pandemic has caused changes to pharmaceutical services activities in community pharmacies, due to various adjustments that must be made. To analyze the impact of COVID-19 pandemic on pharmaceutical service activities in community pharmacies. Cross-sectional approach involving community pharmacist in DKI Jakarta. The quantitative data were collected through distributing online questionnaires in November 2022, while qualitative data were obtained through online in-depth interviews. The quantitative data was analyzed descriptively whereas qualitative data was analyzed using content analysis. Research revealed an increase of 29.4% of pharmacies experiencing out of stock in pharmaceutical supplies compared to before the pandemic. There was a 42.1% decrease indirect Drug Information Services (DIS) compared to before the pandemic. Meanwhile, during the pandmeic a 42.1% increase in online DIS. There were various innovations and strategies done by pharmacies including maximizing the use of digitalization both in the implementation of pharmaceutical services, as well as in promotional activities and online sales of pharmacy productsand. It can be concluded that there are considerable differences in managerial activities and clinical pharmacy services before and during the COVID-19 pandemic, with more digital-based technology involvement in managerial activities and clinical pharmacy services during the pandemic. Keywords: Pharmaceutical services, Pharmacy, COVID-19, Innovations, Strategic